2013
DOI: 10.3390/ijms141122022
|View full text |Cite
|
Sign up to set email alerts
|

Defective Generation and Maturation of Dendritic Cells from Monocytes in Colorectal Cancer Patients during the Course of Disease

Abstract: Colorectal cancer (CRC) is the second-leading cause of cancer-related deaths in Western countries. Today, the role of the host’s immune system in controlling the progression and spread of solid tumors is broadly established. Tumor immunosurveillance escape mechanisms, such as those involving dendritic cells (DCs), the most important antigen-presenting cells, are likewise recognized processes involved in cancer. The present study evaluates the ability of CRC patients to generate DCs in vitro from circulating mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 46 publications
4
30
1
4
Order By: Relevance
“…Orsini et al observed that colorectal cancer patients had deficiency in monocyte-derived DCs differentiation, with reduced expression of co-stimulatory molecules and reduced IL-12 and TNF-α synthesis (38). In our study, no significant changes in the expression of the co-stimulatory molecule CD86 were observed, suggesting that the degree of the cervical lesion was not able to interfere on the expression of this molecule.…”
Section: Discussioncontrasting
confidence: 32%
“…Orsini et al observed that colorectal cancer patients had deficiency in monocyte-derived DCs differentiation, with reduced expression of co-stimulatory molecules and reduced IL-12 and TNF-α synthesis (38). In our study, no significant changes in the expression of the co-stimulatory molecule CD86 were observed, suggesting that the degree of the cervical lesion was not able to interfere on the expression of this molecule.…”
Section: Discussioncontrasting
confidence: 32%
“…The IL-10 was found to be uniquely able to convert fully developed DCs to immature macrophage-like cells in a physiologically highly relevant tumor model in mice [127]. Similarly to this model, patients with colorectal cancer (CRC) are characterized by an increased Tregs-related IL-10 level, while DCs had lower costimulatory molecule expression and were less able to present antigens to allogeneic T cells [128,129]. Although APCs, monocytes, NK cells, T regulatory, and CD8+ lymphocytes are able to exhibit potent antitoxic action against tumor cells, IL-10 mRNA was detected in melanoma-associated macrophages and lymphocytes, suggesting for facilitated evolution of the primary melanoma and rendering of regional lymph nodes susceptible to metastases [118][119][120][121]130].…”
Section: Principal Immune Conditionsmentioning
confidence: 94%
“…An aberrant inflammatory response is a significant cause of morbidity and mortality following a critical insult or surgery . The emergence of a new immunological equilibrium following a critical insult has been proposed as the underlying cause of progressive organ failure, hastened atherosclerosis and resurgence of opportunistic infections . It is uncertain whether postoperative immunological responses to subsequent challenges over an extended period of time are generalisable to all patients .…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, they are a source of dendritic cells, which are crucial to the control of the immune response . Loss of monocyte functional plasticity, heralded by a decreased ability of monocytes to become dendritic cells, signifies an abnormal immune response and is linked to unfavourable outcomes after trauma, pneumonia and cardiac surgery . Thus, monocyte plasticity is significant, and pivotal to the immune response and maintenance of homoeostasis.…”
Section: Introductionmentioning
confidence: 99%